2010
DOI: 10.1364/ol.35.003928
|View full text |Cite
|
Sign up to set email alerts
|

Phase encoding for sharper focus of the azimuthally polarized beam

Abstract: We demonstrate that a sharper focal spot area can be generated (0.147λ(2)) by using an azimuthally polarized beam propagating through a vortex 0-2π phase plate than for radial polarization (0.17λ(2)) or for linear polarization (0.26λ(2)) under the same condition. Further research illustrates that such optimistic results can still be expected when condition limitations are liberalized. This will facilitate new approaches to get superresolution in confocal systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(108 citation statements)
references
References 10 publications
3
100
1
1
Order By: Relevance
“…32,35) Use of LG modes in a combina- tion with HG modes for particle trapping was discussed recently. 127) RP and AP high order LG vector modes have been actively studied due to their capability to generate a small focal spot, 71,73,128) which is attractive for many applications such as super-resolution microscopy or material nano-processing. Scalar LG p0 modes are of interest also due to the perspective of sharp focusing and applications in super-resolution techniques, for 3-D laser prototyping.…”
Section: Resultsmentioning
confidence: 99%
“…32,35) Use of LG modes in a combina- tion with HG modes for particle trapping was discussed recently. 127) RP and AP high order LG vector modes have been actively studied due to their capability to generate a small focal spot, 71,73,128) which is attractive for many applications such as super-resolution microscopy or material nano-processing. Scalar LG p0 modes are of interest also due to the perspective of sharp focusing and applications in super-resolution techniques, for 3-D laser prototyping.…”
Section: Resultsmentioning
confidence: 99%
“…Based on fig. 6 we can infer that the micropolarizer not only convert linearly polarized light into azimuthally polarized beam but also add the phase shift π to diametrically opposite points of the beam [10][11][12][13][14].…”
Section: Transmitting Polarizermentioning
confidence: 93%
“…Nowadays, highly focused beams are present in numerous research areas and technical applications [1][2][3][4][5][6][7][8][9][10]. However, to the best of our knowledge no research has been reported in the field of optical security [11][12][13], using focused fields.…”
Section: Introductionmentioning
confidence: 99%